Method for preparing high-purity quartz sand from quartz ore

Through the method of staged step-by-step treatment and homemade collector flotation, the problems of high impurity content and large acid use in the preparation of high-purity quartz sand are solved, and the preparation of high-purity quartz sand and the reduction of acid use are achieved.

CN119873833AActive Publication Date: 2025-04-25HUAIAN RUIJING QUARTZ TECHNOLOGY CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411818017.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-04-25
Estimated Expiration
2044-12-11

AI Technical Summary

Technical Problem

In the prior art, when preparing high-purity quartz sand, the impurity content of quartz sand is high and a large amount of acid is required for pickling, resulting in high environmental pressure. We need to find a method that can improve the purity of quartz sand and reduce the amount of acid used.

Method used

The staged step-by-step treatment method is adopted, including coarse washing, coarse crushing, direct high-temperature burst water quenching, medium crushing, microwave heating, fine crushing, acid leaching, magnetic separation, flotation and drying. The purity of quartz sand is gradually improved by using homemade collectors, combined with high-temperature burst water quenching and acid leaching and other technical means, and the purity of quartz sand is gradually improved.

Benefits of technology

The high purity preparation of quartz sand is achieved, reducing the amount of acid used, reducing the pressure on the environment, and improving the recovery rate of quartz sand.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a method for preparing high-purity quartz sand from quartz ore, and relates to the field of high-purity quartz sand processing. The preparation method comprises the following steps: firstly, preparing a quaternization cationic reagent by taking benzyl bromide and N, N-dimethyl dodecyl amine as raw materials; adsorption of the self-made collecting agent on the surface of quartz is a result of combined action of electrostatic attraction and multi-form hydrogen bonds, quaternary ammonium groups and polyhydroxy groups are added, and the self-made collecting agent can have high physical adsorption capacity on quartz without strong acid. And a stable filler layer is formed on the surface of the quartz, so that the collecting effect of the quartz sand is improved. Secondly, the preparation process comprises the steps of rough washing, rough crushing, direct-method high-temperature burst water quenching, intermediate crushing, microwave heating, fine crushing, acid leaching, magnetic separation, flotation and drying; by adopting segmented stepped treatment, different treatment means are used for different particle sizes of quartz sand, inclusion in quartz can be removed favorably, and the surface area relative to acid leaching is larger and the effect is better. The quartz sand prepared by the method has the effect of high purity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of high-purity quartz sand processing, in particular to a method for preparing high-purity quartz sand by utilizing quartz ore. Background Art

[0002] Quartz sand is quartz particles formed by crushing quartz stone. Its main component is silicon dioxide. Silicon dioxide is a mineral resource with very stable physical and chemical properties and a wide range of uses. Ordinary quartz sand is used in glass, ceramics, rubber, casting, chemical industry, plastic metallurgy, construction and other fields. High-purity quartz sand usually refers to a silicon dioxide content of more than 99.95%. High-purity quartz sand has excellent chemical stability, high insulation withstand voltage and extremely low volume expansion coefficient. Its high-end products are widely used in large-scale integrated circuits, solar cells, optical fibers, lasers, aerospace, military and other industries. Therefore, the use of various sorting and purification methods to separate high-purity quartz sand from quartz ore resources has become a research focus.

[0003] During the mineralization process of quartz, there are many impurity minerals, such as feldspar, mica, clay minerals, etc. The metal elements such as iron and aluminum in the impurity minerals seriously affect the quality of quartz sand. At present, my country mainly uses high-quality high-purity vein quartz for processing to prepare high-purity quartz sand. The process is relatively simple. The impurity content in large-scale quartz sand is often too much, and the quartz sand content cannot meet the use requirements. The product added value is low. A large amount of acid is used for pickling during the process, especially fluorine-containing hydrofluoric acid, which brings great pressure to the environment. Therefore, it is urgent to find a preparation method for high-purity quartz sand with high quartz sand content and greatly reduced acid usage. The present invention provides a preparation method for high-purity quartz sand using quartz ore to solve the above problems. Summary of the invention

[0004] The object of the present invention is to provide a method for preparing high-purity quartz sand by utilizing quartz ore, so as to solve the problems existing in the prior art.

[0005] In order to solve the above technical problems, the present invention provides the following technical solution: a method for preparing high-purity quartz sand using quartz ore, comprising the following preparation steps:

[0006] (1) Rough washing: Put the quartz ore blocks with a silicon dioxide content of not less than 99.3% as raw materials into a grid box, first put them into a cleaning tank and soak them in clean water for 3 hours, then rinse their surfaces with high-pressure water to remove impurities. Take out the quartz ore blocks with many surface impurities, and rinse them with high-pressure water for a second time to remove impurities. Observe the surface of the quartz ore blocks with the naked eye, and there are no obvious impurities.

[0007] (2) Coarse crushing: The coarsely washed quartz ore is used as raw material and crushed by a jaw crusher to prepare quartz sand with a particle size of 5-15 mm. After screening by a vibrating screen, quartz sand with a particle size of 5-10 mm is obtained;

[0008] (3) Direct method of high temperature explosion water quenching: After the coarsely crushed particles are calcined in a muffle furnace at 400-1400°C, the particles are taken out and placed in a 1:1 mixture of ice and water for quenching for 10-30s, washed once with deionized water, and then soaked in water at a temperature of 40-50°C for 2-4min. After the particles are taken out, they are washed twice with deionized water and dried in a vacuum dryer for 2h;

[0009] (4) Secondary crushing: The quartz sand after water quenching is crushed by a jaw crusher to prepare quartz sand with a particle size of 0.5-5 mm, and then screened by a vibrating screen to obtain quartz sand with a particle size of 0.5-3 mm;

[0010] (5) Microwave heating: The crushed quartz sand is subjected to microwave treatment at 1000-2000W for 15-45min;

[0011] (6) fine crushing: crushing the microwave-treated quartz sand by a fine roller crusher to prepare quartz sand with a particle size of 0.04-0.2 mm, and screening by a vibrating screen to obtain quartz sand with a particle size of 0.06-0.12 mm;

[0012] (7) Acid leaching: Soak the finely crushed quartz sand in a 15-25% by mass hydrochloric acid aqueous solution for 1-3 hours, filter it after soaking, rinse it with deionized water, add a 4-6% by mass sodium carbonate aqueous solution to it and stir it for 0.5-0.8 hours, filter it after the end, rinse the filtered quartz sand with deionized water, and then heat and dry it for 2-5 hours;

[0013] (8) Magnetic separation: Apply a DC electric field with a strength of 200-400 V / cm for 1-2 h, and then apply a magnetic field with a strength of 5000-7000 GS for magnetic separation in a magnetic separator;

[0014] (9) Flotation: quartz sand is placed in a 40 wt% formic acid aqueous solution to prepare a slurry, 15% hydrochloric acid is added to adjust the pH of the slurry to 2-4, and the slurry is stirred and ultrasonicated for 5-15 minutes; 250 g / t of a homemade collector is added to the slurry and stirred for 5-15 minutes; an equal volume of deionized water at 30-35° C. is injected into the slurry, and a frother is added to the slurry at a dosage of 90 g / t, and the slurry is stirred and ultrasonicated for 10-20 minutes; after flotation, the quartz sand is washed with deionized water until it is neutral;

[0015] (10) Drying: Using a far-infrared dryer, the cleaned quartz sand is dried at 200-300° C. for 4-10 h to obtain high-purity quartz sand.

[0016] Furthermore, in step (3), the vacuum degree of the vacuum dryer is -0.095MPa-0.01MPa and the drying temperature is 60°C.

[0017] Furthermore, in step (7), the solid-liquid ratio of quartz sand to hydrochloric acid solution is 1:1.2-1.4.

[0018] Furthermore, in step (7), the solid-liquid ratio of quartz sand to sodium carbonate solution is 1:1.2-1.6.

[0019] Furthermore, the heating and drying in step (7) is performed at 200-300°C.

[0020] Furthermore, in step (8), the magnetic separation temperature is 150-250°C.

[0021] Furthermore, in step (9), the ratio of quartz sand to formic acid aqueous solution is 1:0.5-2.

[0022] Furthermore, in step (9), the stirring speed is 200-300 rpm and the ultrasonic power is 40-60 kHz.

[0023] Furthermore, the preparation method of the homemade collector in step (9) is as follows: N, N-dimethyldodecylamine and benzyl bromide are placed in a reactor at a molar ratio of 1:1.4-3.0, the reactor temperature is maintained at 80-120°C during the quaternization process, the reactor pressure is maintained at 0.1-0.64MPa, the reaction time is 3-5h, the pressure is reduced to 1.4-2.0kPa, and distilled at 50-150°C for 30-120min. During the reaction, an inert gas is used to purge and remove excess reaction gas. The homemade collector is obtained after the reaction is completed.

[0024] Furthermore, in step (9), the foaming agent is triethanolamine dodecylbenzenesulfonate.

[0025] Compared with the prior art, the beneficial effects achieved by the present invention are:

[0026] The invention uses a self-made collector for flotation, and performs segmented and stepped crushing and purification on the quartz ore, so as to achieve the effect of high purity of the prepared quartz sand.

[0027] First, benzyl bromide and N, N-dimethyl dodecylamine are used as raw materials to prepare a quaternary ammonium cationic reagent, the terminal bromine functional group on which has universality and can react with tertiary amine compounds to form quaternary ammonium salts, so as to prepare the self-made collector of the present invention to improve the recovery rate of quartz sand; the adsorption of the self-made collector on the quartz surface is the result of the combined action of electrostatic attraction and multi-form hydrogen bonds, and it adds quaternary ammonium groups and polyhydroxy groups on the basis of dodecylamine collectors, so that the cations can have a strong physical adsorption capacity for quartz without the condition of strong acid during the capture process, and the capture is achieved by electrostatic adsorption. At the same time, the multi-form hydrogen bonds not only enhance the adsorption of the self-made collector on the quartz surface, and the multi-effect synergy with the quartz sand through the hydrogen bond force improves the capture effect, but also enables the self-made collector to form a stable filler layer on the quartz surface, and the long carbon chain of the quaternary ammonium salt organic matter also enhances the hydrophobicity of the quartz surface, thereby improving the capture effect of quartz sand, so as to prepare high-purity quartz sand.

[0028] Secondly, the preparation process of the present invention is coarse washing-coarse crushing-direct high-temperature explosion water quenching-medium crushing-microwave heating-fine crushing-acid leaching-magnetic separation-flotation-drying; a segmented step-by-step treatment is adopted, and different treatment methods are used for different particle sizes of quartz sand. The quartz stone after coarse crushing can expand and shrink more effectively at the overall high temperature during the direct heating process, so that the inclusions inside and outside the quartz sand are more likely to burst. After medium crushing, materials with different dielectric constants will locally produce a large temperature difference during the heating process, so that more cracks are generated on the surface of medium-sized quartz crystals, which can effectively promote the monomer dissociation of minerals and increase the reaction area of ​​impurity minerals, which is beneficial to removing inclusions in quartz; finally, acid leaching is carried out after fine crushing, and the fine particles of quartz sand are more easily soaked in acid to remove impurities therein, and the surface area of ​​relative acid leaching is larger and the effect is better; after this layered treatment, the quartz sand prepared by the present invention has higher purity. DETAILED DESCRIPTION

[0029] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0030] Example 1; (1) Rough washing: a quartz ore block with a silicon dioxide content of not less than 99.3% is placed in a grid box as a raw material block, first placed in a cleaning tank and soaked in clean water for 3 hours, then washed with high-pressure water to remove impurities from its surface, and the quartz ore block with many surface impurities is taken out and washed with high-pressure water for a second time to remove impurities. The surface of the quartz ore block is observed with the naked eye, and no obvious impurities are found;

[0031] (2) Coarse crushing: The coarsely washed quartz ore is used as raw material and crushed by a jaw crusher to prepare quartz sand with a particle size of 5-15 mm. After screening by a vibrating screen, the particle size is 5-10 mm.

[0032] (3) Direct method of high temperature explosion water quenching: the coarsely crushed particles were calcined in a muffle furnace at 400 °C, the particles were taken out and placed in a mixture of ice and water in a ratio of 1:1 for 10 seconds, washed once with deionized water, and then soaked in water at a temperature of 40 °C for 2 minutes. The particles were taken out and washed twice with deionized water, and then dried in a vacuum dryer for 2 hours, with a vacuum degree of -0.095 MPa and a drying temperature of 60 °C.

[0033] (4) Secondary crushing: The quartz sand after water quenching is crushed by a jaw crusher to prepare quartz sand with a particle size of 0.5-5 mm, and then screened by a vibrating screen to obtain quartz sand with a particle size of 0.5-3 mm;

[0034] (5) Microwave heating: The crushed quartz sand was treated with a 1000 W microwave for 15 min;

[0035] (6) fine crushing: crushing the microwave-treated quartz sand by a fine roller crusher to prepare quartz sand with a particle size of 0.04-0.2 mm, and screening by a vibrating screen to obtain quartz sand with a particle size of 0.06-0.12 mm;

[0036] (7) Acid leaching: Soak the finely crushed quartz sand in a 15% hydrochloric acid aqueous solution for 1 hour, with the solid-liquid ratio of quartz sand to the hydrochloric acid solution being 1:1.2. After soaking, filter and rinse with deionized water. Add a 4% sodium carbonate aqueous solution and stir for 0.5 hour, with the solid-liquid ratio of quartz sand to the sodium carbonate solution being 1:1.2. After the end, filter and rinse the filtered quartz sand with deionized water, and then heat and dry for 2 hours at a temperature of 200°C.

[0037] (8) Magnetic separation: Apply a DC electric field with a strength of 200 V / cm for 1 h at a temperature of 150°C, and then apply a magnetic field with a strength of 5000 GS for magnetic separation in a magnetic separator;

[0038] (9) Flotation: Quartz sand is placed in a 40 wt% formic acid aqueous solution to prepare a slurry, the ratio of quartz sand to formic acid aqueous solution is 1:0.5, 15% hydrochloric acid is added to adjust the slurry pH to 2, stirring and ultrasonicating for 5 min, the stirring speed is 200 rpm, and the ultrasonic power is 40 kHz; 250 g / t of a homemade collector is added to the slurry, and stirring is continued for 5 min; an equal volume of deionized water at 30° C. is injected into the slurry, and a foaming agent, triethanolamine dodecylbenzenesulfonate, is added to the slurry at a dosage of 90 g / t, and stirring and ultrasonicating for 10 min , the stirring speed is 200rpm, the ultrasonic power is 40kHz; after flotation, the quartz sand is washed with deionized water to neutrality; the preparation method of the homemade collector is as follows: N, N-dimethyldodecylamine and benzyl bromide are put into a reactor at a molar ratio of 1:1.4, the reactor temperature is maintained at 80°C during the quaternization process, the reactor pressure is maintained at 0.1MPa, the reaction time is 3h, and then the pressure is reduced to 1.4kPa, and distilled at 100°C for 30min. During the reaction, an inert gas is used to purge and remove excess reaction gas, and the homemade collector is obtained after the reaction is completed;

[0039] (10) Drying: The cleaned quartz sand is dried at 200° C. for 4 h using a far-infrared dryer to obtain high-purity quartz sand.

[0040] Example 2; (1) Rough washing: a quartz ore block with a silicon dioxide content of not less than 99.3% is placed in a grid box as a raw material block, first placed in a cleaning tank and soaked in clean water for 3 hours, then washed with high-pressure water to remove impurities from the surface, and the quartz ore block with many surface impurities is taken out and washed with high-pressure water for a second time to remove impurities. The surface of the quartz ore block is observed with the naked eye, and no obvious impurities are found;

[0041] (2) Coarse crushing: The coarsely washed quartz ore is used as raw material and crushed by a jaw crusher to prepare quartz sand with a particle size of 5-15 mm. After screening by a vibrating screen, quartz sand with a particle size of 5-10 mm is obtained;

[0042] (3) Direct method of high temperature explosion water quenching: the coarsely crushed particles were calcined in a muffle furnace at 900 °C, and then the particles were taken out and placed in a mixture of ice and water in a ratio of 1:1 for quenching for 20 seconds, washed once with deionized water, and then soaked in water at a temperature of 45 °C for 3 minutes. After the particles were taken out, they were washed twice with deionized water and dried in a vacuum dryer for 2 hours, with a vacuum degree of -0.095 MPa and a drying temperature of 60 °C.

[0043] (4) Secondary crushing: The quartz sand after water quenching is crushed by a jaw crusher to prepare quartz sand with a particle size of 0.5-5 mm, and then screened by a vibrating screen to obtain quartz sand with a particle size of 0.5-3 mm;

[0044] (5) Microwave heating: The crushed quartz sand was treated with a 1500 W microwave for 30 min;

[0045] (6) fine crushing: crushing the microwave-treated quartz sand by a fine roller crusher to prepare quartz sand with a particle size of 0.12 mm, and screening by a vibrating screen to obtain quartz sand with a particle size of 0.09 mm;

[0046] (7) Acid leaching: Soak the finely crushed quartz sand in a 20% hydrochloric acid aqueous solution for 2 h, with the solid-liquid ratio of quartz sand to the hydrochloric acid solution being 1:1.3. After soaking, filter and rinse with deionized water. Add a 5% sodium carbonate aqueous solution and stir for 0.65 h, with the solid-liquid ratio of quartz sand to the sodium carbonate solution being 1:1.4. After the leaching, filter and rinse the filtered quartz sand with deionized water, and then heat and dry for 3.5 h at 250°C.

[0047] (8) Magnetic separation: applying a DC electric field with a strength of 300 V / cm for 1.5 h at a temperature of 200°C, and then applying a magnetic field with a strength of 6000 GS for magnetic separation in a magnetic separator;

[0048] (9) Flotation: Quartz sand is placed in a 40 wt% formic acid aqueous solution to prepare a slurry, the ratio of quartz sand to formic acid aqueous solution is 1:1.25, 15% hydrochloric acid is added to adjust the pH of the slurry to 3, stirring and ultrasonicating for 10 min, the stirring speed is 250 rpm, and the ultrasonic power is 50 kHz; 250 g / t of a homemade collector is added to the slurry, and stirring is continued for 10 min; an equal volume of deionized water at 32° C. is injected into the slurry, and a foaming agent, triethanolamine dodecylbenzenesulfonate, is added to the slurry at an amount of 90 g / t, stirring and ultrasonicating for 15 min, The stirring speed is 250rpm, and the ultrasonic power is 50kHz; after flotation, the quartz sand is washed with deionized water to neutrality; the preparation method of the homemade collector is as follows: the reactants N, N-dimethyldodecylamine and benzyl bromide are put into a reactor at a molar ratio of 1:2.2, and the reactor temperature is maintained at 100°C and the reactor pressure is maintained at 0.37MPa during the quaternization process. The reaction time is 4h, and then the pressure is reduced to 1.7kPa, and distilled at 100°C for 75min. During the reaction, the excess reaction gas is purged with inert gas to remove the excess reaction gas, and the homemade collector is obtained after the reaction is completed;

[0049] (10) Drying: The cleaned quartz sand is dried at 250° C. for 7 h using a far-infrared dryer to obtain high-purity quartz sand.

[0050] Example 3; (1) Rough washing: a quartz ore block with a silicon dioxide content of not less than 99.3% is placed in a grid box, first placed in a cleaning tank and soaked in clean water for 3 hours, then washed with high-pressure water to remove impurities from the surface, and the quartz ore block with many surface impurities is taken out and washed with high-pressure water for a second time to remove impurities. The surface of the quartz ore block is observed with the naked eye, and no obvious impurities are found;

[0051] (2) Coarse crushing: The coarsely washed quartz ore is used as raw material and crushed by a jaw crusher to prepare quartz sand with a particle size of 5-15 mm. After screening by a vibrating screen, quartz sand with a particle size of 5-10 mm is obtained;

[0052] (3) Direct method of high temperature explosion water quenching: the coarsely crushed particles were calcined in a muffle furnace at 1400 °C, and then the particles were taken out and placed in a mixture of ice and water in a ratio of 1:1 for quenching for 30 seconds, washed once with deionized water, and then soaked in water at a temperature of 50 °C for 4 minutes. After the particles were taken out, they were washed twice with deionized water and dried in a vacuum dryer for 2 hours at a vacuum degree of 0.01 MPa and a drying temperature of 60 °C.

[0053] (4) Secondary crushing: The quartz sand after water quenching is crushed by a jaw crusher to prepare quartz sand with a particle size of 0.5-5 mm, and then screened by a vibrating screen to obtain quartz sand with a particle size of 0.5-3 mm;

[0054] (5) Microwave heating: The crushed quartz sand was treated with a 2000 W microwave for 45 min;

[0055] (6) fine crushing: crushing the microwave-treated quartz sand by a fine roller crusher to prepare quartz sand with a particle size of 0.04-0.2 mm, and screening by a vibrating screen to obtain quartz sand with a particle size of 0.06-0.12 mm;

[0056] (7) Acid leaching: Soak the finely crushed quartz sand in a 25% hydrochloric acid aqueous solution for 3 h, with the solid-liquid ratio of quartz sand to the hydrochloric acid solution being 1:1.4. After soaking, filter and rinse with deionized water. Add a 6% sodium carbonate aqueous solution and stir for 0.8 h, with the solid-liquid ratio of quartz sand to the sodium carbonate solution being 1:1.6. After the leaching, filter and rinse the filtered quartz sand with deionized water, and then heat and dry for 5 h at 300°C.

[0057] (8) Magnetic separation: Apply a DC electric field with a strength of 400 V / cm for 2 h at a temperature of 250°C, and then apply a magnetic field with a strength of 7000 GS for magnetic separation in a magnetic separator;

[0058] (9) Flotation: Quartz sand is placed in a 40 wt% formic acid aqueous solution to prepare a slurry, the ratio of quartz sand to formic acid aqueous solution is 1:2, 15% hydrochloric acid is added to adjust the slurry pH to 4, stirring and ultrasonicating for 15 min, the stirring speed is 300 rpm, and the ultrasonic power is 60 kHz; 250 g / t of a homemade collector is added to the slurry, and stirring is continued for 15 min; an equal volume of deionized water at 35° C. is injected into the slurry, and a foaming agent, triethanolamine dodecylbenzenesulfonate, is added to the slurry at an amount of 90 g / t, stirring and ultrasonicating for 20 min, stirring The speed is 300rpm, and the ultrasonic power is 60kHz; after flotation, the quartz sand is washed with deionized water to neutrality; the preparation method of the homemade collector is as follows: the reactants N, N-dimethyldodecylamine and benzyl bromide are put into a reactor at a molar ratio of 1:3.0, and the reactor temperature is maintained at 120°C and the reactor pressure is maintained at 0.64MPa during the quaternization process. The reaction time is 5h, and then the pressure is reduced to 2.0kPa, and distilled at 150°C for 120min. During the reaction, an inert gas is used to purge and remove excess reaction gas, and the homemade collector is obtained after the reaction is completed;

[0059] (10) Drying: The cleaned quartz sand is dried at 300° C. for 10 h using a far-infrared dryer to obtain high-purity quartz sand.

[0060] Comparative Example 1;

[0061] The difference between Comparative Example 5 and Example 2 is that there are no steps (4) and (6), and the preparation process is changed to: (1) Rough washing: Put the raw material block of quartz with a silicon dioxide content of not less than 99.3% into a grid box, first put it into a cleaning tank and soak it in clean water for 3 hours, then rinse its surface with high-pressure water to remove impurities, take out the quartz ore block with many surface impurities, and perform a secondary high-pressure water impurity removal rinse separately, and observe the surface of the quartz ore block with the naked eye, and no obvious impurities are found;

[0062] (2) Crushing: The roughly washed quartz ore is used as raw material, crushed by a jaw crusher to prepare quartz sand with a particle size of 0.5-5 mm, and then screened by a vibrating screen to obtain quartz sand with a particle size of 0.5-3 mm; then crushed by a fine roller crusher to prepare quartz sand with a particle size of 0.12 mm, and then screened by a vibrating screen to obtain quartz sand with a particle size of 0.09 mm;

[0063] (3) Direct method of high temperature explosion water quenching: the crushed particles were calcined in a muffle furnace at 900 °C, then taken out and placed in a mixture of ice and water in a ratio of 1:1 for quenching for 20 seconds, washed once with deionized water, and then soaked in water at a temperature of 45 °C for 3 minutes. The particles were taken out and washed twice with deionized water, and then dried in a vacuum dryer for 2 hours, with a vacuum degree of -0.095 MPa and a drying temperature of 60 °C.

[0064] (4) Microwave heating: The quartz sand was then treated with a 1500 W microwave for 30 min;

[0065] (5) Acid leaching: The microwave-heated quartz sand was soaked in a 20% hydrochloric acid aqueous solution for 2 h, with a solid-liquid ratio of quartz sand to the hydrochloric acid solution of 1:1.3. After soaking, the quartz sand was filtered and rinsed with deionized water. A 5% sodium carbonate aqueous solution was added thereto and stirred for 0.65 h, with a solid-liquid ratio of quartz sand to the sodium carbonate solution of 1:1.4. After the leaching, the quartz sand was filtered and rinsed with deionized water, and then heated and dried for 3.5 h at a temperature of 250°C.

[0066] (6) Magnetic separation: Apply a DC electric field with a strength of 300 V / cm for 1.5 h at a temperature of 200 °C, and then apply a magnetic field with a strength of 6000 GS for magnetic separation in a magnetic separator;

[0067] (7) Flotation: Quartz sand is placed in a 40 wt% formic acid aqueous solution to prepare a slurry, the ratio of quartz sand to formic acid aqueous solution is 1:1.25, 15% hydrochloric acid is added to adjust the slurry pH to 3, stirring and ultrasonicating for 10 min, the stirring speed is 250 rpm, and the ultrasonic power is 50 kHz; 250 g / t of a homemade collector is added to the slurry, and stirring is continued for 10 min; an equal volume of deionized water at 32° C. is injected into the slurry, and a foaming agent, triethanolamine dodecylbenzenesulfonate, is added to the slurry at a dosage of 90 g / t, and stirring and ultrasonicating for 15 min , the stirring speed is 250rpm, the ultrasonic power is 50kHz; after flotation, the quartz sand is washed with deionized water to neutrality; the preparation method of the homemade collector: the reactants N, N-dimethyldodecylamine and benzyl bromide are put into the reactor at a molar ratio of 1:2.2, the reactor temperature is maintained at 100°C during the quaternization process, the reactor pressure is maintained at 0.37MPa, the pressure is reduced to 1.7kPa, and distilled at 100°C for 75min. During the reaction, the excess reaction gas is purged with inert gas, the reaction time is 4h, and the homemade collector is obtained after the reaction is completed;

[0068] (8) Drying: Use a far-infrared dryer to dry the cleaned quartz sand at 250° C. for 7 hours to obtain high-purity quartz sand. The remaining steps are the same as those in Example 2.

[0069] Comparative Example 2

[0070] The difference between Comparative Example 5 and Example 2 is that step (9) is different, and step (9) is changed to: flotation: quartz sand is placed in a formic acid aqueous solution with a mass fraction of 40wt% to prepare a slurry, the ratio of quartz sand to formic acid aqueous solution is 1:1.25, 15% hydrochloric acid is added to adjust the pH of the slurry to 3, stirring and ultrasonicating for 10 minutes, the stirring speed is 250rpm, and the ultrasonic power is 50kHz; 250g / t of dodecylamine is added to the slurry, and stirring is continued for 10 minutes; an equal volume of deionized water at 32°C is injected into the slurry, and a foaming agent, triethanolamine dodecylbenzenesulfonate, is added to the slurry in an amount of 90g / t, stirring and ultrasonicating for 15 minutes, the stirring speed is 250rpm, and the ultrasonic power is 50kHz; after flotation, the quartz sand is washed with deionized water until neutral; the remaining steps are the same as those in Example 2.

[0071] Effect example

[0072] Table 1 below shows the performance analysis results of preparing high-purity quartz sand using quartz ore using Examples 1 to 3 of the present invention and Comparative Examples 1 to 2.

[0073] Table 1

[0074] <![CDATA[ SiO 2(%)]]> <![CDATA[ Al 2 O 3(%)]]> <h2 style=";text-align:left;direction:ltr"><![CDATA[ <h2 style=";text-align:left;direction:ltr"> F <h2 style=";text-align:left;direction:ltr"> e2<h2 style=";text-align:left;direction:ltr"> O <h2 style=";text-align:left;direction:ltr"> 3(%)]]><h2 style=";text-align:left;direction:ltr"> Example 1 99.997 0.0003 0.0002 Example 2 99.999 0.0001 0.0002 Example 3 99.998 0.0002 0.0002 Comparative Example 1 99.985 0.0007 0.0009 Comparative Example 2 99.972 0.0015 0.0013

[0075] From the experimental data comparison of the percentage content of silicon dioxide in the embodiment and the comparative example, it can be found that the present invention uses benzyl bromide and N, N-dimethyl dodecylamine as raw materials to prepare a quaternary ammonium cationic reagent, and the terminal bromine functional group thereon has universality, and can react with tertiary amine compounds to form quaternary ammonium salts, so as to prepare the homemade collector of the present invention to improve the recovery rate of quartz sand; the adsorption of the homemade collector on the quartz surface is the result of the combined action of electrostatic attraction and multi-form hydrogen bonds, and it adds quaternary ammonium groups and polyhydroxy groups on the basis of the dodecylamine collector, so that the cation can have a stronger physical adsorption capacity to quartz without the condition of strong acid in the capture process, and capture is achieved by electrostatic adsorption. At the same time, multi-form hydrogen bonds not only enhance the adsorption of the homemade collector on the quartz surface, and improve the capture effect through the multi-effect synergy of hydrogen bond force with quartz sand, but also make the homemade collector form a stable filler layer on the quartz surface, and the long carbon chain of the quaternary ammonium salt organic matter also enhances the hydrophobicity of the quartz surface, thereby improving the capture effect of quartz sand, to prepare high-purity quartz sand. Secondly, the preparation process of the present invention is coarse washing-coarse crushing-direct high-temperature explosion water quenching-medium crushing-microwave heating-fine crushing-acid leaching-magnetic separation-flotation-drying; a segmented step-by-step treatment is adopted, and different treatment methods are used for different particle sizes of quartz sand. The quartz stone after coarse crushing can expand and shrink more effectively at the overall high temperature during the direct heating process, so that the inclusions inside and outside the quartz sand are more likely to burst. After medium crushing, materials with different dielectric constants will locally produce a large temperature difference during the heating process, so that more cracks are generated on the surface of medium-sized quartz crystals, which can effectively promote the monomer dissociation of minerals and increase the reaction area of ​​impurity minerals, which is beneficial to removing inclusions in quartz; finally, acid leaching is carried out after fine crushing, and the fine particles of quartz sand are more easily soaked in acid to remove impurities therein, and the surface area of ​​relative acid leaching is larger and the effect is better; after this layered treatment, the quartz sand prepared by the present invention has higher purity.

[0076] It will be apparent to those skilled in the art that the invention is not limited to the details of the exemplary embodiments described above and that the invention can be implemented in other specific forms without departing from the spirit or essential features of the invention. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description, and it is intended that all variations within the meaning and scope of the equivalent elements of the claims be included in the invention. Any marking in a claim should not be considered as limiting the claim to which it relates.

Claims

1. A method for preparing high-purity quartz sand using quartz ore, characterized in that: The method comprises the following preparation steps: (1) Rough washing: Put the quartz ore blocks with a silicon dioxide content of not less than 99.3% as raw materials into a grid box, first put them into a cleaning tank and soak them in clean water for 3 hours, then rinse their surfaces with high-pressure water to remove impurities. Take out the quartz ore blocks with many surface impurities, and rinse them with high-pressure water for a second time to remove impurities. Observe the surface of the quartz ore blocks with the naked eye, and there are no obvious impurities. (2) Coarse crushing: The coarsely washed quartz ore is used as raw material and crushed by a jaw crusher to prepare quartz sand with a particle size of 5-15 mm. After screening by a vibrating screen, quartz sand with a particle size of 5-10 mm is obtained; (3) Direct method of high temperature explosion water quenching: After the coarsely crushed particles are calcined in a muffle furnace at 400-1400°C, the particles are taken out and placed in a 1:1 mixture of ice and water for quenching for 10-30s, washed once with deionized water, and then soaked in water at a temperature of 40-50°C for 2-4min. After the particles are taken out, they are washed twice with deionized water and dried in a vacuum dryer for 2h; (4) Secondary crushing: The quartz sand after water quenching is crushed by a jaw crusher to prepare quartz sand with a particle size of 0.5-5 mm, and then screened by a vibrating screen to obtain quartz sand with a particle size of 0.5-3 mm; (5) Microwave heating: The crushed quartz sand is subjected to microwave treatment at 1000-2000 W for 15-45 min; (6) fine crushing: crushing the microwave-treated quartz sand by a fine roller crusher to prepare quartz sand with a particle size of 0.04-0.2 mm, and screening by a vibrating screen to obtain quartz sand with a particle size of 0.06-0.12 mm; (7) Acid leaching: Soak the finely crushed quartz sand in a 15-25% by mass hydrochloric acid aqueous solution for 1-3 hours, filter it after soaking, rinse it with deionized water, add a 4-6% by mass sodium carbonate aqueous solution to it and stir it for 0.5-0.8 hours, filter it after the end, rinse the filtered quartz sand with deionized water, and then heat and dry it for 2-5 hours; (8) Magnetic separation: Apply a DC electric field with a strength of 200-400 V / cm for 1-2 h, and then apply a magnetic field with a strength of 5000-7000 GS for magnetic separation in a magnetic separator; (9) Flotation: quartz sand is placed in a 40 wt% formic acid aqueous solution to prepare a slurry, 15% hydrochloric acid is added to adjust the pH of the slurry to 2-4, and the slurry is stirred and ultrasonicated for 5-15 minutes; 250 g / t of a homemade collector is added to the slurry and stirred for 5-15 minutes; an equal volume of deionized water at 30-35° C. is injected into the slurry, and a frother is added to the slurry at a dosage of 90 g / t, and the slurry is stirred and ultrasonicated for 10-20 minutes; after flotation, the quartz sand is washed with deionized water until it is neutral; (10) Drying: Using a far-infrared dryer, the cleaned quartz sand is dried at 200-300° C. for 4-10 h to obtain high-purity quartz sand.

2. The method for preparing high-purity quartz sand from quartz ore according to claim 1, characterized in that: In the step (3), the vacuum degree of the vacuum dryer is -0.095MPa-0.01MPa and the drying temperature is 60°C.

3. The method for preparing high-purity quartz sand from quartz ore according to claim 1, characterized in that: In the step (7), the solid-to-liquid ratio of quartz sand to hydrochloric acid solution is 1:1.2-1.

4.

4. The method for preparing high-purity quartz sand from quartz ore according to claim 1, characterized in that: In the step (7), the solid-to-liquid ratio of quartz sand to sodium carbonate solution is 1:1.2-1.

6.

5. The method for preparing high-purity quartz sand from quartz ore according to claim 1, characterized in that: The heating and drying in step (7) is performed at 200-300°C.

6. The method for preparing high-purity quartz sand from quartz ore according to claim 1, characterized in that: The magnetic separation temperature in step (8) is 150-250°C.

7. The method for preparing high-purity quartz sand from quartz ore according to claim 1, characterized in that: In the step (9), the ratio of quartz sand to formic acid aqueous solution is 1:0.5-2.

8. The method for preparing high-purity quartz sand from quartz ore according to claim 1, characterized in that: In the step (9), the stirring speed is 200-300 rpm and the ultrasonic power is 40-60 kHz.

9. The method for preparing high-purity quartz sand from quartz ore according to claim 1, characterized in that: The method for preparing the homemade collector in step (9) is as follows: N,N-dimethyldodecylamine and benzyl bromide are placed in a reactor at a molar ratio of 1:1.4-3.0; during the quaternization process, the reactor temperature is maintained at 80-120°C, the reactor pressure is maintained at 0.1-0.64MPa, the reaction time is 3-5h, the pressure is reduced to 1.4-2.0kPa, and distilled at 50-150°C for 30-120min. During the reaction, inert gas is used to purge and remove excess reaction gas; and the homemade collector is obtained after the reaction is completed.

10. The method for preparing high-purity quartz sand from quartz ore according to claim 1, characterized in that: In the step (9), the foaming agent is triethanolamine dodecylbenzenesulfonate.

Citation Information

Patent Citations

  • Preparation method of highly pure quartz sands

    CN105948062A

  • Collecting agent composition for quartz sand purification

    CN109499771A

  • Microwave magnetizing roasting-gradient magnetic separation iron removal method and purification process for quartz ore

    CN119076205A

  • Process for preparing and processing high-purity quartz sand from quartz ore with high iron and aluminum content

    CN119080008A

  • Collecting agent for antiflotation desilicification and preparing method thereof

    CN1507954A